THE EFFECT OF POST-PRODUCTION SHELF TIME ON THE ANTIOXIDANT ACTIVITY OF SOY MILK - Fadhillah; Nazip, Khoiron; Meilinda (BRIN - Badan Riset dan Inovasi Nasional, 2025)
This study was conducted to analyze the effect of post-production storage time on antioxidant activity in soy milk. Antioxidants are compounds that can ward off free radicals, so it is important to know their stability over time. The storage time used in this study was 1, 4, 7, 10, and 13 hours post-production. Antioxidant activity testing was carried out using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Qualitatively, the color change of the DPPH solution was observed from purple to light yellow, while quantitatively the absorbance value was measured using UV-Vis Spectrophotometry. The inhibition value and IC50 were calculated to determine the strength of antioxidant activity in soy milk. The results showed that soy milk with a storage time of 1 hour had the best antioxidant activity with an IC50 value of 28.19 μg/ml which was classified as very strong. At 4 hours of storage time, the IC50 value of 37.28 μg/ml is classified as moderate, while at 7 hours and 10 hours the IC50 values ​​were 146.95 μg/ml and 119.38 μg/ml, respectively, which are also classified as moderate. At 13 hours, the antioxidant activity decreased drastically with an IC50 value of 228.90 μg/ml, which is classified as very weak. The antioxidant activity of soy milk decreased with increasing storage time. Factors such as temperature, light, and components of soy milk contribute to the degradation of antioxidant activity. Therefore, consumption of soy milk should be done within a shorter time after production to obtain optimal antioxidant benefits.